Climatic yield potential of Japonica‐type rice in the Korean Peninsula under RCP scenarios using the ensemble of multi‐GCM and multi‐RCM chains. (12th August 2020) - Ahn, Joong‐Bae; Kim, Young‐Hyun; Shim, Kyo‐Moon; Suh, Myoung‐Seok; Cha, Dong‐Hyun; Lee, Dong‐Kyou; Hong, Song‐You; Min, Seung‐Ki; Park, Seong‐Chan; Kang, Hyun‐Suk
Abstract: Rice production in the Korean Peninsula (KP) in the near future (2021–2050) is analysed in terms of the climatic yield potential (CYP) index for Japonica‐type rice. Data obtained from the dynamically downscaled daily temperature and sunshine duration for the Historical period (1981–2010) and near future under two Representative Concentration Pathway (RCP4.5 and RCP8.5) scenarios are utilized. To reduce uncertainties that might be induced by using a Coupled General Circulation Model (CGCM)—a Regional Climate Model (RCM) chain in dynamical downscaling, two CGCM—three RCM chains are used to estimate the CYP index. The results show that the mean rice production decreases, mainly due to the increase of the temperature during the grain‐filling period (40 days after the heading date). According to multi model ensemble, the optimum heading date in the near future will be approximately 12 days later and the maximum CYP will be even higher than in the Historical. This implies that the rice production is projected to decrease if the heading date is selected based on the optimum heading date of Historical, but to increase if based on that of near future. The mean rice production during the period of ripening is projected to decrease (to about 95% (RCP4.5) and 93% (RCP8.5) of the Historical) in the western and southern regions of the KP, but to increase (to about 104% (RCP4.5) and 106% (RCP8.5) of the Historical) in the northeastern coastal regions of the KP. However, if the optimum heading date is selected in the near future climate, the peak rice production is projected to increase (to about 105% (RCP4.5) and 104% (RCP8.5) of the Historical) in the western, southern and northeastern coastal regions of the KP, but to decrease (to about 98% (RCP4.5) and 96% (RCP8.5) of the Historical) in the southeastern coastal regions of the KP. Abstract : Peak rice production is projected to increase (to about 105% (RCP4.5) and 104% (RCP8.5) of the Historical; red colour) in the western, southern and northeastern coastal regions of the Korean Peninsula, but to decrease (to about 98% (RCP4.5) and 96% (RCP8. 5) of the Historical; blue colour) in the southeastern coastal regions of the Korean Peninsula, if the optimum heading date is selected approximately 12 days later than the Historical period in the near future.